Callus Induction of Leaves and Stems in Krisan (Chrysanthemum morifolium Ramat cv Dewi ratih) with Alternative Foliar Fertilizers Media - Naser, Ahmad Saifun; Wisnu, Muhammad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2020)
Availability of quality seeds in production of krisan (Chrysanthemum morifolium Ramat cv Dewi ratih) cultivation is still rare, therefore research on seed multiplication through tissue culture is needed. The media used in tissue culture is relatively expensive for home industry. This study aims to determine the respond of leaf and stem explants using foliar fertilizers (Growmore, Gandasil D and Mutiara) as an alternative media for callus inductions. This study used a Completely Randomized Design (CRD) consisted of 4 treatments: P0: Â½ MS + 0,25 mg/l BAP, P1 (Growmore + 0,25 mg/l BAP), P2 (Gandasil D + 0,25 mg/l BAP), P3 (Mutiara + 0,25 mg/l BAP). The variables observed in this study included callus appearance time, callus color and callus texture. The result of this study indicated that the use of BAP (6-Benzyl Amino Purine) affected the time of callus formation and callus morphology. Callus was formed on leaf explants 13 days after planting while on stem explants 7 days after planting and compact texture. Growmore + 0,25 mg/l BAP treatment yields the best callus on leaf explant, while Gandasil D + 0,25 mg/l BAP treatment yields the best callus on stem explant.